(untitled) (CIPEEX, 2026)
Introduction: Osteoarthritis is a common joint disease that primarily affects the knee joint, causing pain, difficulty moving, and limited quality of life. Advanced age, female gender, high body mass index, and previous injuries to the affected segment are significant risk factors. Although there is no known cure, treatments can help alleviate symptoms and preserve joint mobility. Method: A descriptive integrative review was conducted to assess the impact of the disease on the daily lives of the elderly population. Ten articles were selected and analyzed, demonstrating several interventions that can be effective in relieving symptoms, including reducing pain, physical function, muscle strength, and balance. Results: Effective treatments included intra-articular injections, platelet-rich plasma (PRP), rowing exercises with monitored and restricted blood flow, transcutaneous vagal stimulation, elastic taping, nutritional supplementation, Tai Chi Chuan, and cabbage leaf therapy. Conclusion: These findings suggest that non-pharmacological methods and alternative therapies can be leveraged in disease management, improving well-being and reducing impairments in patients’ physical function. These results may contribute to improving the health of older adults with knee osteoarthritis, highlighting the importance of a multidisciplinary and personalized approach to meet individual needs.